37th Aerospace Sciences Meeting and Exhibit 1999
DOI: 10.2514/6.1999-206
|View full text |Cite
|
Sign up to set email alerts
|

Initial growth rate and visual characteristics of a round jet into a sub- to supercritical environment of relevance to rocket, gas turbine, and diesel engines

Abstract: Public reporting burden lor this eolation of information is estimated to average 1 hour per respo-se n-udrg ~e . ~e ■-• revewng instructions, searching existing datasources gathering and maintaining the data needed, and completing and reviewing this collection of information Send ccmme-fs recarcna tr s ouroen estimate or any other aspect of this collection of information including suggestions for reducing this burden to Department of Defense. Washington Headquarters Se vices Directorate tor Info-mation Abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 14 publications
5
56
0
Order By: Relevance
“…Studies at DLR have also included reacting flows. Details of each facility can be found in the respective authors' previous publications, many of which are listed in the extensive references provided at the end of this paper , Chehroudi et al (1999Chehroudi et al ( -2004, Davis and Chehroudi (2004), Decker et al (1998), Mayer et al ( -2003, Oschwald et al (1999Oschwald et al ( -2002). However, adequate information regarding the facility, injector geometries, and diagnostics used is necessary in order to better understand the results presented here and to make this paper reasonably selfsufficient and complete.…”
Section: Test Benches and Experimental Setupsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies at DLR have also included reacting flows. Details of each facility can be found in the respective authors' previous publications, many of which are listed in the extensive references provided at the end of this paper , Chehroudi et al (1999Chehroudi et al ( -2004, Davis and Chehroudi (2004), Decker et al (1998), Mayer et al ( -2003, Oschwald et al (1999Oschwald et al ( -2002). However, adequate information regarding the facility, injector geometries, and diagnostics used is necessary in order to better understand the results presented here and to make this paper reasonably selfsufficient and complete.…”
Section: Test Benches and Experimental Setupsmentioning
confidence: 99%
“…Therefore, Froude number values were calculated for the AFRL facility at each condition. As an example, Chehroudi et al (1999Chehroudi et al ( , 2002 showed that for their experiments the Froude number ranges from 42,000 to 110,000. Chen and Rodi (1980) suggested that the flow is momentum dominated when a defined length scale x b is less than 0.53, while Papanicolaou and List (1988) …”
Section: Jet Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, the mechanisms controlling injection and mixing under these conditions were not well understood, even to the extent that significant qualitative questions existed. However, considerable progress has been made over the past decade by research performed under this task [1][2][3][4][5][6][7][8][9][10][11][12] as well as by others [13][14][15][16][17].…”
Section: Sponsoring / Monitoring Agency Name(s) and Address(es)mentioning
confidence: 99%